Utilization of alugbati (Basella alba 'Rubra'), squash (Cucurbita maxima), mung bean (Vigna Radiata) sprouts, and tomatoes (Lycopersicon esculentum) in dehydrated vegetable soup mix production. - Magsucang, Nyrelle Love Dela Cerna
Protein-energy malnutrition and micronutrient deficiencies have led the nutritional problems in the Philippines since 1998. This study was conducted to develop dehydrated instant soup mix to aid in fighting malnutrition and iron deficiency in the country. An instant dehydrated vegetable soup mix was developed using dried vegetables such as alugbati, squash, mung bean sprouts, and tomatoes with garlic and salt as other ingredients. The results obtained from the Kruskal-Wallis test at 95% confidence interval, showed that the vegetable soup mix formulations significantly differed with each other in terms of preference. Formulation 2 was deemed most preferable and was characterized by proximate analysis, physico-chemical analysis and sensory evaluation. Proximate analysis revealed that the most preferred formulation (F2) contained 6.43 ± 0.14% moisture, 8.84 ± 0.12% protein, 15.81 ± 0.17% ash, 2.59 ± 0.16% fat, 1.43 ± 0.28% fiber, and 65.00 ± 0.475 carbohydrates while physico-chemical analysis revealed that the MPF possessed 0.44 ± 0.01 water activity, 4.76 ± 0.15 pH, 0.2847 mg Fe/g iron content, 625 kg/m3 bulk density, and 318.6512 kcal/g. The vegetable soup mix in this study has an appreciable amount of protein and iron for children ages 1-3 years old, 20% of the RDA for children 4-8 years old and 25% of the RDA for children 9-13 years old. The results of the cost of production analysis reveals that the unit price for the vegetable soup mix is Php 2.58 per serving (7g). This is comparable to commercially available products (Knorr Cream of Mushroom) which costs Php41.00 per pack (71g). The general acceptability of the most preferred vegetable soup mix was rated "like moderately" indicating that the product has a potential for commercialization.